Screening of Fungi from Oil Palm Rhizosphere in Peat Soils and the Potential as Biological Agents against Ganoderma boninense - Puspita, Fifi; Dini, Isna Rahma; Sari, Dermala (Indonesian Journal of Agricultural Research, 2019)
One of the diseases that attack oil palm plants is stem rot disease. Control efforts that can be done is to use rhizosphere fungi from oil palm plants in peat soils. This study aimed to select fungi from rhizosphere of oil palm plants in peat soil based on morphological characteristics and test their potential as biological agents against Ganoderma boninense. This research was conducted by exploration, observation and experiment by using complete randomized design (RAL). The parameters observed were macroscopic characteristics of fungi from oil palm rhizosphere, disease severity index, fungus inhibition power from oil palm rhizosphere to G. boninense, colony diameter and growth rate of high antagonist rhizosphere fungus, hyperparasitic type of fungus from rhizosphere of oil palm plant with G. boninense and the morphological characteristics of fungi from high antagonist rhizosphere in macroscopic and microscopic. The results showed that 12 rhizosphere fungi isolates and 4 isolates were antagonist to G. boninense. Isolate J5 has a high antagonist power of 70.26% and is a genus Trichoderma, isolate J7 belongs to the genus Trichoderma, isolate J10 genus Aspergillus and isolate J12 genus Mucor.